2016
DOI: 10.1021/acs.analchem.6b00704
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Sorting Endothelial and Neural Progenitors from Human Induced Pluripotent Stem Cells by Sedimentation Field Flow Fractionation

Abstract: Human induced pluripotent stem cells (hiPSc) are a very useful solution to create and observe the behavior of specific and usually inaccessible cells, such as human motor neurons. Obtained from a patient biopsy by reprograming dermal fibroblasts (DF), hiPSc present the same properties as embryonic stem cells and can generate any cell type after several weeks of differentiation. Today, there are numerus protocols which aim to control hiPSC differentiation. The principal challenge is to obtain a sufficiently enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…In addition, calcitriol is involved in various processes, such as neural stem cell differentiation, axon genesis, and the growth of MNs [48]. Furthermore, the high purity of the cells obtained with this protocol could be further improved by sedimentation field flow fractionation (SdFFF), which makes it possible to obtain neural and endothelial precursors after spontaneous differentiation in basic medium, with no added factors [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcitriol is involved in various processes, such as neural stem cell differentiation, axon genesis, and the growth of MNs [48]. Furthermore, the high purity of the cells obtained with this protocol could be further improved by sedimentation field flow fractionation (SdFFF), which makes it possible to obtain neural and endothelial precursors after spontaneous differentiation in basic medium, with no added factors [49].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, larger and less dense cells generating more hydrodynamic lift forces within the mobile phase and not very sensitive to centrifugal force (blue cells on Figure 5A ), will be eluted before smaller and denser cells (red cells, Figure 5A ) generating less hydrodynamic forces and more sensitive to the multigravitational field. As for a number of other cell models [ 27 , 29 , 31 ], we found that under the elution conditions, U87 cells were eluted under the hyperlayer elution mode [ 28 , 30 ] schematized in Figure 5A .…”
Section: Resultsmentioning
confidence: 73%
“…A pioneering study of CSCs sorting from within a GB cell line [ 28 ] made it possible to sort other cancer cells [ 29 ] and to improve cell culture conditions ahead of cell sorting and CSCs detection [ 30 ]. Moreover, these studies allowed an opening towards the field of stem cell biology [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The usually described SdFFF elution mode for cells is the "hyperlayer" mode 22,23,32,33 in which subpopulations of cells are focused into a thin layer at an equilibrium position in the channel thickness, depending on their biophysical properties: size and density as first-order parameters, along with shape and rigidity. 24 Hyperlayer elution order is size-and density-dependent: larger and less dense cells are focused in the faster streamlines, and are consequently eluted first. The experimental retention ratio, R obs (void time divided by retention time [t 0 / t R ], measured by the first moment method) 34 , was calculated to determine the average velocities and elution modes.…”
Section: Tools and Methodology For Cell Crossover Frequency Measurementmentioning
confidence: 99%
“…One of the most interesting label-free cell sorting methods is the now well-known sedimentation field-flow fractionation (SdFFF) technique. [22][23][24] . The SdFFF is a gentle and noninvasive technique.…”
Section: Introductionmentioning
confidence: 99%